Harnessing UV radiation for enhanced agricultural production: benefits on nutrition, quality, and sustainability - Gideon Sadikiel Mmbando (All Life)
Ultraviolet (UV) has a significant impact on the health and development of plants. Depending on the wavelength, UV is divided into three regions according to their wavelengths: UVC (less than 280 nm), UVB (280-315 nm), and UVA (315-400 nm). Although high UV levels have been shown to harm plant growth, low doses of UV stimulate the synthesis and buildup of healthy compounds that absorb UV, and it has positive effects on the nutritional value and productivity of various fruits, ornamental crops, and vegetables. However, there is little recent data on the use of UV radiation to improve the quality of agricultural production. This review discusses various UVA, UVB, and UVC radiation applications for pre- and post-harvest agricultural production improvement. Both UVA and UVB boost plant resilience to environmental pressures by increasing their antioxidant power through the manufacturing of secondary metabolites like flavonoids and phenolics. UVC radiation has strong germicidal qualities that improve the quality of fruits and the shelf life of fresh foods, which is something that consumers who prefer healthy, organic food urgently need right now. This review offers essential knowledge and methods for using UV radiation as a safe tool to increase global food security.